From Stress to Confidence: A Self-Efficacy Approach to Reading and Writing Instruction for Pre-Service Kindergarten and Primary Educators - Chasanatun, Fida; Malawi, Ibadullah; Utari, Sindy Mey Dwi (Profesi Pendidikan Dasar, 2024)
This study investigated the role of self-efficacy in shaping reading and writing competencies among pre-service kindergarten and primary educators, with implications for pedagogical strategies to address skill deficiencies. Focusing on second-semester students enrolled in an English for Academic Purposes course, a cohort of 146 participants was randomly selected from a population of 274. Employing a mixed-methods approach—integrating quantitative surveys and quasi-experimental pre-post tests—the intervention incorporated self-selected reading materials aligned with individual comprehension levels, resulting in a 22.6% to 38.4% increase in confidence and reading engagement. Schema- and table-based instructional tasks demonstrated significant improvements in comprehension and motivation. Furthermore, mandating the integration of 3–5 academic references in writing assignments transformed students’ perceptions of literacy tasks from stress-inducing to intellectually valuable, yielding a 37% rise in positive attitudes and a 38.6% enhancement in self-efficacy. When extended to third-semester cohorts, structured lecturer guidance utilizing tabular frameworks was highlighted as a distinctive pedagogical feature